HYGIENIC ASSESSMENT OF WORKING CONDITIONS AND OCCUPATIONAL RISK IN COAL INDUSTRY WORKERS - Кислицына, Вера Викторовна; Суржков, Дмитрий Вячеславович; Пестерева, Дина Викторовна; Мотуз, Ирэна Юрьевна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2023)
The aim of the research was to assess the risk of developing occupational diseases in coal pit workers based on the hygienic characteristics of working conditions in order to develop preventive measures.Materials and methods. The indices of dust content, noise, vibration and microclimate at the workplaces of miners of the Kaltansky coal pit located in the South of the Kemerovo region were analyzed. Factors of the labor process were assessed on the basis of SanPiN 1.2.3685-21; classes of working conditions were determined in accordance with Guideline P 2.2.2006-05; occupational risks were calculated according to the method of Mikhailuts A.P. et al.Results. A significant excess of the permissible noise level was detected at the workplaces of excavator and drilling rig operators, bulldozer operators, drivers of auxiliary equipment and dump trucks. Operators of excavators and drilling rigs were exposed to high levels of whole-body vibration of category II (transport and technological). The most unfavorable working conditions in terms of the level of vibration impact were found at the workplaces of bulldozer operators. The level of dust content, which significantly exceeded the hygienic standard, was determined at the workplaces of dump truck drivers. Also, an increased level of dust content was registered at the workplace of bulldozer operators. Taking into account the combined effect of production factors, the working conditions of excavator drivers, drilling rig operators, blasters, drivers of auxiliary vehicles were assigned to the 3rd class of the 2nd degree. The 3rd class of the 3rd degree included the working conditions of bulldozer drivers, drivers of BelAZ dump trucks, road workers and repair personnel. Bulldozer operators had the highest risk of developing occupational diseases due to exposure to noise and vibration. The greatest risk of developing dust pathology was found in the workplaces of drivers of BelAZ dump trucks.Conclusion. Based on the definition of harmfulness and hazard classes of the production environment and the levels of occupational risk to the health of coal pit workers, a system of medical and preventive measures has been developed and implemented.
Keywords: coal pit; working conditions; occupational risk